How Coretax Perceptions and Tax Penalties Affect Annual Tax Return Filing Compliance - Imanuel Ebenhaezer Dethan; Christianus Yudi Prasetyo (Forum Kerjasama Pendidikan Tinggi, 2026)
Beyond the strategic role of taxation as a primary source of government revenue, the government continues to pursue digital transformation through the implementation of the Coretax system to improve taxpayer compliance. This study examines the influence of perceived ease of use and perceived usefulness of Coretax on Annual Tax Return filing compliance among individual taxpayers in the Greater Jakarta area in 2026, with tax penalties acting as a moderating variable. This study employs a quantitative approach using primary data collected through online questionnaires distributed via Google Forms to 100 respondents selected using convenience sampling. The data were analyzed using Moderated Regression Analysis (MRA). The results show that perceived ease of use negatively affects Annual Tax Return filing compliance (β = -0.864; p = 0.046), whereas perceived usefulness has a positive effect (β = 1.571; p < 0.001). In addition, tax penalties do not moderate the relationship between perceived ease of use and compliance (p = 0.066) but negatively moderate the relationship between perceived usefulness and compliance (β = -0.089; p = 0.005). These findings suggest that the functional benefits of Coretax are an important factor in encouraging taxpayer compliance, while technological convenience that is not supported by taxpayer discipline may lead to delayed filing behavior.